Anomaly of digastric muscle: an alarm bell for head and neck surgeon - Rosati, Valentina; Petruzzi, Gerardo; Campo, Flaminia; Mazzola, Francesco; Sequino, Giulio; oliva, Flavia; Oliva, Gaspare; Pellini, Raul; Ricciardiello, Filippo (Acta Biomedica Atenei Parmensis, 2021)
Objectives: Here follows the discussion of a case of hypoplasia of both bellies of digastric muscle and the difficult during neck dissection, because of his surgical importance like a pivotal landmark.Methods: We reported a case report concerning digastric muscle abnormalities, accidentally discovered during neck dissection due to surgical excision of a glottic squamous cell carcinoma staged as cT3N0. A brief literature review was done to compare and research similar cases.Results: Literature counts several reports of digastric muscle abnormalities, namely involving the anterior belly. Little has been written about hypoplasia of digastric muscle.Conclusion: Digastric muscle abnormalities are rare, which can be absent or, more frequently, duplicated. Albeit its anomalies are anecdotal, it is advisable to give due consideration to the hypoplasia of both bellies of the digastric muscle during the analysis of radiological imaging, in order to prevent the risk of operative complications. According to our knowledge, this is the first and singular case of digastric muscle’s hypoplasia.